Study of the Ultilization of Crustacean Waste into Commercial Chitosan Products - Syafni, Diana; Prastari, Cindytia (Jurnal Perikanan Terpadu, 2025)
Seafood shell waste from restaurants is often discarded or used as animal feed, despite its considerable untapped economic potential. One promising high-value utilization is processing this waste into chitosan, a biopolymer widely demanded in the pharmaceutical, cosmetic, and agricultural industries. This study aims to assess the financial potential of producing chitosan from seafood shell waste in small businesses. We gathered 500 grams of shell waste from multiple seafood restaurants in Pekanbaru over the course of seven days. The waste was NaOH solution stirred for 90 minutes at 70°C. The resulting Vannamei shrimp chitosan was a white powder with 2.8% moisture content and solubility in acetic acid. Meanwhile, the chitosan derived from mangrove crab shells appeared as an off-white powder with 4.34% moisture content, also soluble in acetic acid. We conducted an economic analysis by calculating the total production cost and comparing it to the market prices of chitosan on various e-commerce platforms. The results indicate that the chitosan produced has a significantly higher market value than its production cost. These findings indicate that seafood shell waste is not merely an environmental issue but also a promising economic opportunity for MSMEs. Waste-to-chitosan conversion presents an innovative strategy to promote circular economy principles and empower small-scale enterprises.